2010
DOI: 10.1055/s-0030-1259017
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Porphyrin-Catalyzed Carbenoid Transfer Reactions

Abstract: R u t h e n i u m -P o r p h y r i n -C a t a l y z e d C a r b e n o i d T r a n s f e r R e a c t i o n s CongAbstract: Ruthenium-porphyrins are effective catalysts for a wide variety of carbenoid transfer reactions, such as alkene cyclopropanation, carbon-hydrogen, nitrogen-hydrogen, or sulfur-hydrogen (X-H, X = C, N, S) bond insertion, diazo coupling, carbonyl or azomethine ylide formation/1,3-dipolar cycloaddition, and halonium, sulfonium, or ammonium ylide formation/[2,3]-sigmatropic rearrangement reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…4). In this reaction, EDA reacts with the Ru(II) ion to extrude an N 2 molecule to yield an electrophile αestercarbenoid intermediate, [41][42][43][44][45][46][47] which undergoes a nucleophile attack 54,55 by another EDA molecule to afford a double-bond after a second extrusion of an N 2 molecule. As already discussed above, carbene axial ligands can exercise strong kinetic trans-effects in Ru (II)porphyrinates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). In this reaction, EDA reacts with the Ru(II) ion to extrude an N 2 molecule to yield an electrophile αestercarbenoid intermediate, [41][42][43][44][45][46][47] which undergoes a nucleophile attack 54,55 by another EDA molecule to afford a double-bond after a second extrusion of an N 2 molecule. As already discussed above, carbene axial ligands can exercise strong kinetic trans-effects in Ru (II)porphyrinates.…”
Section: Resultsmentioning
confidence: 99%
“…In the present communication, we use macrocycle 1 as ligand for Ru(II) ions to prepare macrocyclic endotopic complexes with a more extensive catalytic scope as acyclic Ru(II)porphyrinates are known [41][42][43][44][45][46][47] to promote a wide variety of carbene transfer/insertion reactions such as cyclopropanation, 1,3-dipolar cycloadditions, X-H (X = C, N, O, and S) insertions, olefination of aldehydes in the presence of phosphines and dimerization of diazo synthons.…”
mentioning
confidence: 99%
“…Thus, rhodium(II)-catalysed decomposition of 2-diazo-6-methylthio-3-oxohexanoate 11a gave the stable six-ring sulfonium ylide 20 in practically quantitative yield. It has recently been reported that ruthenium(II) porphyrins are suitable catalysts for carbenoid sulfonium ylide formation as well [43]. In continuation of our comparative studies of dirhodium(II,II) tetracarboxylate and tetracarbonyldiruthenium(I,I) complexes [44], we found that the saccharinato complex [Ru 2 (CO) 5 [μ-sac) 2 ] 2 [45], the acetato complex [Ru 2 (CO) 4 (μ-OAc) 2 ] n and the trinuclear ruthenium(0) complex Ru 3 (CO) 12 (3 mol % of catalyst in each case) gave yields of 74, 69, and 49% for the conversion of 11a to 20 .…”
Section: Resultsmentioning
confidence: 99%